2013
DOI: 10.1016/j.plefa.2013.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of docosahexaenoic acid supplementation during pregnancy on fetal heart rate and variability: A randomized clinical trial

Abstract: DHA (22:6n-3) supplementation during infancy has been associated with lower heart rate (HR) and improved neurobehavioral outcomes. We hypothesized that maternal DHA supplementation would improve fetal cardiac autonomic control and newborn neurobehavior. Pregnant women were randomized to 600 mg/day of DHA or placebo oil capsules at 14.4 (+/−4) weeks gestation. Fetal HRand HRV were calculated from magnetocardiograms (MCGs) at 24, 32 and 36 weeks gestational age (GA). Newborn neurobehavior was assessed using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 41 publications
2
43
1
Order By: Relevance
“…Three of these studies did not observe beneficial effects of supplementation on the overall cognitive test scores at 18 months [24] or 6.5 years of age [33], or on visual development at 3-6 or 4 months of age [34,35]. A study in 67 pregnant women given a daily supplement of 600 mg DHA/day observed higher fetal heart rate variability measured at 24, 32, and 36 weeks of gestation and higher scores on a newborn neonatal behavioral assessment scale [36]. A study in 48 pregnant women in the USA who consumed cereal-based DHA-fortified food during pregnancy observed fewer sleep arousals in the infants of supplemented women, which the authors identified as an early marker of improved neurodevelopment [37].…”
Section: Resultsmentioning
confidence: 99%
“…Three of these studies did not observe beneficial effects of supplementation on the overall cognitive test scores at 18 months [24] or 6.5 years of age [33], or on visual development at 3-6 or 4 months of age [34,35]. A study in 67 pregnant women given a daily supplement of 600 mg DHA/day observed higher fetal heart rate variability measured at 24, 32, and 36 weeks of gestation and higher scores on a newborn neonatal behavioral assessment scale [36]. A study in 48 pregnant women in the USA who consumed cereal-based DHA-fortified food during pregnancy observed fewer sleep arousals in the infants of supplemented women, which the authors identified as an early marker of improved neurodevelopment [37].…”
Section: Resultsmentioning
confidence: 99%
“…Although no findings in this area are yet definitive, this pattern of results is consistent with effects attributable to the presence of LCPUFA or DHA in the individual’s diet, rather than to an early programming effect. Our group has shown previously that fetal HR variability is increased by prenatal DHA supplementation with 600 mg/d of DHA (28) and higher HR variability is linked to cognitive measures such as arousal and attention (29), but to our knowledge a link between fetal HR variability and cognitive function in infancy has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The first category included behavioral measures of peak look duration and number of looks to habituation; look duration has been reported to be affected by DHA status in one study of prenatal maternal supplementation (9) but not in a subsequent clinical trial of postnatal feeding (23). The second category was infants’ heart rate (HR) during the various points of the habituation protocol, which has been shown to be affected by postnatal supplementation (23, 28). The third category reflected a coupling of behavior and HR (39, 40), and included the proportion of time spent in HR-defined phases of attention.…”
Section: Methodsmentioning
confidence: 99%
“…59 Positive associations between DHA supplementation and offspring neurodevelopment in another RCT were observed only when the odds of scoring in the highest range as a function of DHA levels in cord blood were tested. 60 Other RCTs of DHA supplementation during pregnancy have resulted in higher heart rate variability and higher scores on the neonatal behavioral assessment scale 61 and in more protected sleep during the neonatal period. 62 In the DHA to Optimize Mother Infant Outcome Study, a large RCT of DHA supplementation in a community sample of pregnant Australian women, supplementation resulted in fewer preterm births.…”
Section: Evidence For An Association Between Docosahexaenoic Acid Levmentioning
confidence: 99%